2018
DOI: 10.1093/scan/nsy045
|View full text |Cite
|
Sign up to set email alerts
|

The resilient brain: psychological resilience mediates the effect of amplitude of low-frequency fluctuations in orbitofrontal cortex on subjective well-being in young healthy adults

Abstract: Psychological resilience reflects the capacity to bounce back from stress, which plays an important role in health and well-being. However, less is known about the neural substrate for psychological resilience and the underlying mechanism for how psychological resilience enhances subjective well-being in the healthy brain. To investigate these issues, we employed fractional amplitude of low-frequency fluctuations (fALFF) measured with resting-state fMRI in 100 young healthy adults. The correlation analysis fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 91 publications
(137 reference statements)
0
56
0
Order By: Relevance
“…The SFG is generally considered a core brain region in the cognitive control system (Niendam et al, 2012) and for emotion regulation-related processes (Frank et al, 2014), which are hypothesized to be crucial for perceived stress that emphasizes the subjective cognitive and emotional adjustment for objective stressors (Cohen et al, 1983;Phillips, 2012). Additionally, the positive association of the fALFF in the left SFG with perceived stress may reflect a compensatory mechanism to counteract functional or structural brain abnormalities (Bing et al, 2013;Kong et al, 2018;Orr et al, 2013;Wang, Zhao, et al, 2018), which might be linked to the outcomes or difficulties induced by higher levels of perceived stress.…”
Section: Discussionmentioning
confidence: 99%
“…The SFG is generally considered a core brain region in the cognitive control system (Niendam et al, 2012) and for emotion regulation-related processes (Frank et al, 2014), which are hypothesized to be crucial for perceived stress that emphasizes the subjective cognitive and emotional adjustment for objective stressors (Cohen et al, 1983;Phillips, 2012). Additionally, the positive association of the fALFF in the left SFG with perceived stress may reflect a compensatory mechanism to counteract functional or structural brain abnormalities (Bing et al, 2013;Kong et al, 2018;Orr et al, 2013;Wang, Zhao, et al, 2018), which might be linked to the outcomes or difficulties induced by higher levels of perceived stress.…”
Section: Discussionmentioning
confidence: 99%
“…If the OFC and precuneus became more strongly connected, conservatives were more likely to be resilient to psychological stress and have greater self-regulation capacity, specifically impulse control and causal reasoning. The OFC is one of key regions involved in self-regulation and psychological resilience, while the precuneus processes emotion regulation as coactivated with the amygdala 24,41,42 . The connectivity between these regions is related to the self-processing of negative emotional distractors and mental representation 29 .…”
Section: Scientific Reportsmentioning
confidence: 99%
“…We cleaned noise signals by conducting nuisance regression using a component-based noise correction method (CompCor), linear detrending, and temporal bandpass filtering (0.008 < f < 0.09 Hz) 69,70 . functional connectivity analysis. To investigate seed-based functional connectivities, we selected the regions of interest (ROIs) according to previous neuroimaging studies reporting brain function in self-regulation and psychological resilience as follows: the ACC, amygdala, insula, and OFC 10,14,24,39 . The ROIs were defined using the Harvard-Oxford cortical and subcortical atlases.…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of focusing on pathology, research on positive neuroscience directs its attention on the neural mechanisms supporting flourishing, psychological well-being, resilience, and promotion of health. Previous studies have investigated the structural and functional neural basis underlying positive human functioning such as well-being (e.g., Van Reekum et al, 2007;Heller et al, 2013;Kong et al, 2015a;Sato et al, 2015), meditation (e.g., Cahn and Polich, 2006;Sperduti et al, 2012), optimism (e.g., De Pascalis et al, 2013, resilience (e.g., Kong et al, 2015bKong et al, , 2018, and creativity (e.g., Fink et al, 2009), based on experimental and self-reported measures. However, this emerging literature is just the tip of the iceberg on the quest to identify the complex mechanisms of brain structure and function supporting human behavior.…”
Section: Positive Neuroscience: the Neuroscience Of Human Flourishingmentioning
confidence: 99%